METHODS FOR IMPROVING THE QUALITY OF VIDEO INFORMATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The above methods for improving the quality and accuracy of video information preprocessing make it possible to expand the scope of using video information processing devices in various sectors of the national economy. Improving the quality of video processing creates the necessary prerequisites for increasing the reliability of image recognition and the accuracy of optical measurements.